2020
DOI: 10.1016/j.cub.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Niche Cell Wrapping Ensures Primordial Germ Cell Quiescence and Protection from Intercellular Cannibalism

Abstract: Highlights d Niche cell wrapping templates a laminin-based basement membrane around the gonad d Basement membrane and dystroglycan maintain niche cell wrapping d Basement membrane inhibits Notch to ensure primordial germ cell quiescence d Niche cell wrapping protects primordial germ cells from cannibalism by neighboring cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…However, this phenotype does not likely relate to DAF-18 since, unlike PGC divisions in the daf-18 mutant [5], loss of akt-1 does not suppress PGC divisions that occur upon depletion of laminin. Rather, inappropriate PGC divisions are dependent on GLP-1 Notch signaling [71]. We examined our RNA-seq dataset and found that both sygl-1 and lst-1 (the relevant outputs of GLP-1 signaling) are indeed detected but their levels are not significantly different in starved daf-18 mutants versus wild type.…”
Section: Plos Geneticsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this phenotype does not likely relate to DAF-18 since, unlike PGC divisions in the daf-18 mutant [5], loss of akt-1 does not suppress PGC divisions that occur upon depletion of laminin. Rather, inappropriate PGC divisions are dependent on GLP-1 Notch signaling [71]. We examined our RNA-seq dataset and found that both sygl-1 and lst-1 (the relevant outputs of GLP-1 signaling) are indeed detected but their levels are not significantly different in starved daf-18 mutants versus wild type.…”
Section: Plos Geneticsmentioning
confidence: 95%
“…However, these divisions likely reflect defects in fate specification [65] rather than alterations in levels of germline transcripts. In addition, depletion of the basement membrane component laminin allows PGCs to divide [71]. However, this phenotype does not likely relate to DAF-18 since, unlike PGC divisions in the daf-18 mutant [5], loss of akt-1 does not suppress PGC divisions that occur upon depletion of laminin.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…During embryogenesis, the constitutive activation of NOTCH1 signaling in Sertoli cells caused the exit of gonocyte from the quiescence status [26]. In flies, Notch signaling directly controls germline stem cell development and maintenance [5,63], reinforcing the importance of cell-to-cell Notch signaling in the regulation of germ cell differentiation. Interestingly, although our results in medaka support the activation of the Notch pathway, including receptors, ligands, γ-secretase and the respective effectors of this pathway, the activation of Notch signals seems to work in the opposite direction to that described above, wherein the input signal (high temperature) seems to be sensed by SGa while the output seems to be in the somatic cells with a high expression of Pen-2, presumably Sertoli cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, despite countless studies, it is still difficult to characterize the somatic stem niche in v e r t e b r a t e s [ 1 7 ] . R e c e n t s t u d i e s i n e a r l y development of mice have been able to show a possible somatic stem niche [18], and much progress has also been made in other model organisms, like flies [5,6]. In both cases, it was observed that one of the main signaling pathways involved is the Notch pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation